Measurement of the longitudinal structure function and the small x gluon density of the proton - Cooper-Sarkar, A; Ingelman, G; Long, K; Roberts, R; Saxon, D (Springer-Verlag, 1988)
At HERA energies the small x region (x≲10 -2) can be explored at Q 2 values large enough that leading twist QCD calculations are valid. We show how measurement of the longitudinal structure function, F L(x,Q 2), can lead to accurate measurement of the gluon structure function at such small x values. Experimental systematic errors are discussed fully and requirements for the measurement outlined. We conclude that it should be possible to distinguish between the widely varying gluon distributions which are currently allowed. © 1988 Springer-Verlag.